PENERAPAN METODE PEMBELAJARAN PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW (PQ4R) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V UPTD SDN 229 PINRANG - Abdul Halik; Muslimin; Nurkhafifah Kasau (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this study is the low reading comprehension ability of fifth grade students of UPTD SDN 229 Pinrang, especially in the subject of Indonesian. This study aims to determine the improvement of the learning process and students' reading comprehension ability through the application of the Preview, Question, Read, Reflect, Recite, Review (PQ4R) Learning Method. The approach used in this study is a qualitative approach with the type of research, namely classroom action research (PTK). Data collection techniques used in this study are observation, tests and documentation. The subjects of the study were teachers and fifth grade students totaling 12 students consisting of 8 female students and 4 male students. The study was conducted in two cycles, in cycle I the results of the study on the learning process were in sufficient qualification (C) and the results of the evaluation test were in sufficient qualification (C). Cycle II the results of the study on the learning process were in good qualification (B) and the results of the evaluation test were in good qualification (B). The conclusion in this study is that the application of the Preview, Question, Read, Reflect, Recite, Review (PQ4R) learning method can improve the learning process and reading comprehension ability of fifth grade students of UPTD SDN 229 Pinrang.